Seafloor mosaic objects modeling and recognition - Ramašauskas, Olegas; Janulevičius, Vytautas; Vaitkus, Aurimas; Kazlauskas, Mantas (Lietuvos matematikos rinkinys, 2014)
Providing Klaipeda University Marine Sciences and Technology Centre instruments which are developed for seafloor digital image analysis, object recognition in the heterogeneous environment, and evaluate the results of work. The paper describes a robotic-submarine gathered image enhancement, underwater image mosaic texture and colours description, area segmentation and filtering algorithms and their software components.